Nutritional and potential health benefits of chufa oil, olive oil, and anhydrous milk fat against gallstone disease in a C57BL/6N mouse model - Zommara, Mohsen A.; Swelam, Seham; Raya-Álvarez, Enrique; Imaizumi, Katsumi; Elmahdy, Ahmed; Alkhudhayri, Dalal A.; Aljehani, Abeer A.; Agil, Ahmad; Elmahallawy, Ehab Kotb (Frontiers in Nutrition, 2024)
Dietary lipids play a major role in many diseases, particularly cardiovascular diseases. Recently, the health value of plant oils, particularly heart health, has been recognized. Despite these facts, limited information is available on the potential nutritional and anti-arteriolosclerosis effects of chufa oil, olive oil, and anhydrous milk fat in C57BL/6N mice. In the present study, the effects of olive oil (OO), chufa oil (CO), and anhydrous milk fat (AMF) on 4-week-old C57BL/6N male mice, a model for studies of diet-induced atherosclerosis, were investigated. The AIN-93G-based diet was supplemented with 15% of either OO, CO, or AMF. The final mixture of the diets contained 15% fat, approximately 1.25% cholesterol, and 0.5% sodium cholate. The data obtained showed that most mice had gallstone disease. The highest percentage of the gallstones formed were found in AMF groups (approximately 85.7% of the mice). However, the lowest one was found in the chufa oil group (42.9%), followed by the olive oil group (57.1%). Although the mice's food intake significantly differed, their body weights did not change during the feeding period. The diet supplemented with CO resulted in a significant reduction in serum cholesterol compared with the other groups. Livers from the CO-fed group showed higher triglyceride levels than those from the AMF group. No significant differences were found in atherosclerotic lesions in the aortic valve between the groups. Collectively, our results show no deleterious nutritional effects of the fats used on C57BL/6N mice fed cholesterol-rich diets. Chufa oil improved cholesterol metabolism and atherogenic index in mice. However, the major issue is the formation of gallstones in all mice, which is most prominent in AMF, followed by olive oil and chufa oil diets.